Impact of Improving Quality of Dialysis Fluid on Oxidative Stress and Lipid Profile in Hemodialysis Patients. (19th December 2012) - Elkabbaj, Driss; Bahadi, Abdelali; Cherrah, Yahia; Errasfa, Mourad; Eljaoudi, Rachid
Abstract : The aim of this study was to evaluate the levels of malondialdehyde as an oxidative stress marker in the same hemodialysis patients after changing the quality of dialysate with ultrapure dialysis fluid. Methods . This prospective study concerns hemodialysis patients; all patients were in the first step treated with conventional dialysate, and in the second step (three months later) the same patients were treated with online produced ultrapure dialysis fluid. The malondialdehyde, C-reactive protein, total cholesterol, triglycerides, high-density lipoprotein, low-density lipoprotein, fibrinogen, and albumin were quantified before the two steps. Results . Thirty-seven patients completed the study. Ultrapure dialysis fluid reduced but not significantly the malondialdehyde concentrations. Both dialysis fluids were associated with improvement in the malondialdehyde level before and after the hemodialysis session. In lipid parameters, there was a significant decrease with conventional dialysis fluid versus ultrapure dialysis fluid of triglycerides, total cholesterol, and high-density lipoprotein in patients' blood. Instead, the level of low-density lipoprotein, fibrinogen, albumin, and C-reactive protein does not change significantly. Conclusion . The lipid parameters were improved for triglycerides and total cholesterol. Malondialdehyde increases following the hemodialysis session, and the conventional dialysate increased malondialdehyde levels more than the ultrapure dialysis but the differences were not statistically significant.